(untitled) (Mongolian Journal of Arts and Culture, 2025)
This study aims to identify the connection between the bowing technique of the Morin khuur and traditional Mongolian games (flicking in shagai shooting and the bow grip in archery). It further seeks to compare the features of the traditional Mongolian bowing style with that of Inner Mongolian Morin khuur players, focusing on differences in sound production and articulation. The study analyzed the electric signals of the Morin khuur tones, comparing the physical characteristics such as the frequencies and sound levels of the fundamental and overtone components. The main finding is that the energy distribution of sound signals in the Inner Mongolian technique is more dispersed, while in the Mongolian technique, the energy concentration is more stable. This indicates that the Mongolian bow-hold produces clearer and better-quality sound. A total of 146 students and staff from a professional institution participated in the research. Among the professional players surveyed, nearly all (99%) using the Inner Mongolian bow-hold, while more than half (52.5%) stated that it is necessary to learn the Mongolian bow-hold technique. Most students expressed a need for Morin khuur lessons to be provided online and supported with audio and video materials. The study concluded that there is a pressing need to preserve and pass on the traditional bowing culture to future generations. It is also recommended that professional Morin khuur players, universities, professional institutions, and training centers raise awareness of the advantages of the traditional Mongolian bow-hold and continue conducting further research and analysis. Уламжлалт монгол барилаар хуурдах онцлогийг харьцуулан туршсан нь Хураангуй: Энэхүү судалгааны ажлаар морин хуурын хуурдах арга барил нь монголчуудын уламжлалт тоглоом наадгайтай (шагай харвааны нясалгаа, сур харвааны нумын барил) уялдсан байдлыг тодруулж, улмаар уламжлалт монгол барилын онцлог болон Өвөр монгол морин хуурчдын нумын хоёр барилыг харьцуулж, дуугаралт, хэллэгийг тодорхойлохыг зорьсон. Морин хуурын эгшгүүдийн цахилгаан дохиог судалж, үндсэн болон дагалдах өнгүүдийн давтамж, дуугаралтын түвшин зэрэг физик шинжүүдийг харьцуулсан болно. Эгшгүүдийн дуугаралтын цахилгаан дохионы үзүүлэлтүүд өвөр монгол барилын хувьд энергийн төвлөрөл сарнилт ихтэй бол монгол барилын хувьд энергийн төвлөрөл тогтвортой байна гэсэн гол үр дүн гарлаа. Энэ нь монгол барил дуугаралт цэвэр,сайн байгааг харуулж байна. Судалгаанд мэргэжлийн байгууллагын нийт 146 оюутан, ажилтан хамрагдсан. Судалгаанд оролцсон мэргэжлийн хуурчид 99% нь өвөр монгол нумын барилаар хуурдаж байгаа бол 52.5% хувь нь монгол нумын барил сурах шаардлагатай гэж хариулжээ. Оюутнуудын хувьд дийлэнх нь морин хуурын хөгжмийн хичээлийг цахим хэлбэрээр оруулсан байх, түүнчлэн аудио, видео бичлэг шаардлагатай гэжээ. Эдгээрээс хуурдах соёлыг хойч үедээ өвлүүлэн үлдээж, мэргэжлийн морин хуурчид, их, дээд сургууль, мэргэжлийн байгууллага, морин хуурын сургалтын төвүүдэд уламжлалт монгол нумын барилын давуу талыг танин мэдүүлж, цаашид судалгаа, шинжилгээ хийх шаардлагатай гэж үзлээ. Түлхүүр үгс: нумын барил, дуугаргалтын энергийн тархалт, цохилго, хуурын татлага, нумын хэмжээс